(untitled) (Research, Society and Development, 2022)
This research aimed to evaluate the opportunities and challenges of using the Portfolio for evaluation in higher education, especially in the remote context at the end of the semester of activities of the Research Group Educational Paradigms and Teacher Training, from the Theory and Practice line Pedagogy in teacher training. The objective was to evaluate the opportunities and/or challenges of using portfolio assessment in higher education, especially in the application of remote teaching. Having as a problem: How to think about the evaluation of the learning of higher education students, in the face of a global pandemic, who started to have their academic activities carried out remotely? It is qualitative research of the research-training type. The group consisted of 8 doctoral university professors and 2 mediating doctoral professors from a large private university. Four responded to the questionnaire used to collect data for the research. The results were positive, as even the challenges were recognized as helping the group’s growth and learning.